Beyond formula American film genres - Solomon, Stanley J. (San Diego Harcourt Brace Jovanovich, Inc., 1976)
Covers westerns, musicals, horror films, detective/mystery films, gangster films, and war films.
Introduction -- Defining genre -- Genre and popular culture -- 1. The western as myth and romance -- Landscape -- Movement -- The romance of the West -- The lonely hero -- Sheriffs and marshals -- The outlaw and the gangster -- Stagecoach (1939) -- Winchester '73 (1950) ; Shane (1953) -- Johnny Guitar (1954) -- The searchers (1956) -- Comanche station (1960) -- The wild bunch (1969) -- Butch Cassidy and the Sundance Kid (1969) -- 2. Singing and dancing: the sound of metaphor -- The metaphorical mode -- The procedures of metaphor -- Categories of the genre -- Filmmakers -- The theory of integration -- Thematic integration: A star is born and An American in Paris -- A note on the musical theater -- Gold diggers of 1933 (1933) -- Top hat (1935) -- Swing time (1936) -- The pirate (1948) -- Singin' in the rain (1952) -- The band wagon (1953) -- Funny girl (1968) -- Cabaret (1972)-- 3. The nightmare world. Fears and horrors -- The cinema of reason and nightmare -- The terror of the plausible: an aspect of science fiction films -- Irrational terrors -- Romantic isolation -- Some minor categories -- King Kong (1933) -- The bride of Frankenstein (1935) -- Invasion of the body snatchers (1956) -- Psycho (1960) -- The birds (1963) -- Night of the living dead (1968) -- Rosemary's baby (1968) -- The exorcist (1973) -- 4. The life of crime. The categories of criminal films -- The gangster mind -- Criminal values -- Prisoners -- The public enemy (1931) -- Force of evil (1949) -- White heat (1949) -- Riot in Cell Block 11 (1954) -- On the waterfront (1954) -- Bonnie and Clyde (1969) -- The godfather (1972) -- 5. The search for clues. Categories of investigation -- Procedures of detection -- Motivation -- Police professionalism -- The private detective myth -- The Maltese falcon (1941) -- The big sleep (1946) -- Harper (1966) -- Bullitt (1968) -- Klute (1971) -- Dirty Harry (1972) -- Chinatown (1974) -- 6. Wars: hot and cold. War as an attitudinal genre -- War as propaganda -- The antiwar film -- War in the air -- Was as background -- Victims of war -- Exiles and isolated heroes -- Spies and secret agents -- Hell's angels (1936) -- Gone with the wind (1939) -- To be or not be (1942) -- Casablanca (1942) -- Paths of glory (1957) -- North by northwest (1959) -- Dr. Strangelove, or How I learned to stop worrying and love the bomb (1963) -- Patton (1970)
Includes bibliographical references (pages 296-298) and indexes.
Keywords: Motion pictures -- United States; Film genres